2020
DOI: 10.26440/ihrj/0403.06172
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Addiction: Case Report of a Young Adult

Abstract: Pregabalin has been used widely for the treatment of neuropathic pain, generalized anxiety disorders and epilepsy. Data is scarce and much is not known about the addictive potential of pregabalin. Herein, we report details of a young adult who got addicted to pregabalin and approached for a smooth withdrawal. The subject had a successful outcome. Literature suggests a growing concern for the abuse of pregabalin. Risk factors associated with the development of addictive behavior with pregabalin need to be asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Thematic map analysis showed that the subject of "opioids" was a motor theme in research on pregabalin addiction. The emergence of opioids as a motor theme, one of the trend topics of the last three years, may be due to the effect of pregabalin on reducing opioid withdrawal syndrome (1). According to the results of a study, 39 of 440 individuals using opioids were found to use pregabalin (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thematic map analysis showed that the subject of "opioids" was a motor theme in research on pregabalin addiction. The emergence of opioids as a motor theme, one of the trend topics of the last three years, may be due to the effect of pregabalin on reducing opioid withdrawal syndrome (1). According to the results of a study, 39 of 440 individuals using opioids were found to use pregabalin (23).…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin is a new-generation antiepileptic that reduces the emission of multiple stimulants by reducing the calcium flux induced by depolarization (1). It is indicated for use in epilepsy, peripheral neuropathic pain, fibromyalgia, generalized anxiety disorder, and post-herpetic neuralgia (2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregabalin is a new-generation antiepileptic that reduces multiple stimulus output by reducing depolarization-induced calcium flux (16). It is indicated for the treatment of epilepsy, peripheral neuropathic pain, fibromyalgia, postherpetic neuralgia, chronic pruritus, restless legs syndrome, generalized anxiety disorder and insomnia (17,18).…”
Section: Introductionmentioning
confidence: 99%